Biografi Mejar Jeneral Dato’ Haji Muhammad Mudzamir Ong Bin Abdullah / Nik Afikah Mohamad Mran ... [et al.] - Mohamad Mran, Nik Afikah; Khairi, Nur Azlin; Samsudin, Ahmad Zam Hariro; Mat Isa, Azman; Abu Bakar, Amzari (Fakulti Pengurusan Maklumat, UiTM Kampus Puncak Perdana, 2020)
This article based on the life history of an air force officer named Major General Dato’ Haji Muhammad Mudzamir Ong Bin Abdullah, the first navigator to serve as a Major General in the Royal Malaysian Air Force (RMAF). His experience and challenges in the military can be able to inspire the community especially among youth who wants to challenge themselves in pursuit of life to serve their country. This article is based on an oral source of an interview and literatures. His story begins with his background, a young man living in the village, his military life, experience as a pioneer, international involvement and contribution to organization as well as the awards received.